Peran Kebijakan Moneter Menurunkan Tingkat Inflasi di Indonesia - Riska, Elvina; Siregar, Erma Hotnijar; Anthony, Bayu Hady (Universitas Negeri Yogyakarta, 2025)
This study aims to see how the role of conventional and Islamic monetary policy on reducing inflation in Indonesia. This study is a qualitative study with literature studies, data obtained through books and journals related to the research discussed. The results of this study indicate that the government's way to reduce the inflation rate conventionally is by issuing SBI (Bank Indonesia Certificate) or SBIS (Bank Indonesia Sharia Certificate) if using sharia methods. For further researchers if using the same title, the researcher recommends using qualitative research with the latest data.